Dalihan Na Tolu Sebagai Konsep Dasar Rancangan Jembatan Tano Ponggol (Studi Kelayakan Jembatan Tano Ponggol) - Purboyo, Wiryawan (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2021)
Lake Toba National Tourism Strategic Area (NTSA) requires tourism relevant road and bridge to support tourism. For this reason, the road segment for Tele - Pangururan - Nainggolan - Onan Runggu - Lagundi - Tomok - Ambarita - Pangururan was implemented and plans to build the Tano Ponggol Bridge in Pangururan District, Samosir Regency as land access to Samosir Island. The government plans to replace the Tano Ponggol bridge as well as make it a landmark for Pangururan Tourism City. The local wisdom approach to the bridge design is put on the concept of kinship which is owned by all ethnic groups around the Lake Toba area. The principles of the kinship concept in Batak culture are: Dalihan Na Tolu: elek marboru, somba marhula hula, and manat mardongan tubu. These three principles are manifested in the design of a three-legged bridge. The results of the multi-criteria analysis show that the greatest value in alternative 3, namely replacing the main pilon bridge and cable stayed bridge using a concrete box structure 47.5+95+47.5 m (the erection balance cantilever method), the architectural aesthetic concept "Dalihan Na Tolu” with the construction of three symmetrical parallel pillars as bridge accessories, so that the purpose the bridge design which is also a landmark can still be achieved.